Sources of Western knowledge of the thought of Hassan Hanafi: References (methodologies) - Safar, Sarab Mohammed; Saleh, Hussein Hadi (Al-Adab Journal, 2021)
Hassan Hanafi was influenced by Western philosophers, especially Espinosa, Feuerbach and Husserl, by adopting their ideas and methods and applying them to the religious phenomenon. Referring to the original texts instead of taking the authority of the clergy to reveal the relationship between theology and politics. And then Feuerbach’s materialism, whose centrality revolves around the attempt to humanize religion and to eliminate the idealistic and contemplative philosophies on which religion depends and its call to eliminate human alienation through the return of the individual to his human qualities that he attributed to God and thus his independence of mind and will, “The future has no religion.